Design and experimental implementation of voltage control scheme using the coefficient diagram method based PID controller for two-level boost converter with photovoltaic system - Latreche, Kamel; Taleb, Rachid; Bentaallah, Abderrahim; Toubal Maamar, Alla Eddine; Helaimi, M'hamed; Chabni, Fayçal (Національний технічний університет "Харківський політехнічний інститут", 2024)
Introduction. Currently, in the solar energy systems and a variety of electrical applications, the power converters are essential part. The main challenge for similar systems is controller design. In the literature, the PID controller has proved its effectiveness in many industrial applications, but determining its parameters remains one of the challenges in control theory field. The novelty of the work resides in the design and experimental implementation of a two-level boost DC-DC converter controlled by a PID controller for photovoltaic (PV) maximum power extraction. Purpose. Analysis and control of the two-level boost topology with renewable energy source and design of the PID controller parameters using simple and accurate method. Methods. PID coefficients are optimized using Coefficient Diagram Method (CDM) in the MATLAB environment. Results. A mathematical model of a two-level boost converter with PID controller and PV energy source was developed and analyzed. The model allows to design the controller parameters of the proposed system. Practical value. A prototype steered by the proposed CDM-PID controller was tested using an Arduino embedded board. A comparison between the simulation results and the experimental one is presented. The obtained results illustrate that the experimental results match the simulation closely, and the proposed CDM-PID controller provides a fast and precise results. References 24, table 2, figures 16.

В даний час перетворювачі потужності є невід'ємною частиною сонячних енергетичних систем та різних електричних пристроїв. Основною проблемою для таких систем є проектування контролера. У літературі ПІД-регулятор довів свою ефективність у багатьох промислових застосуваннях, але визначення його параметрів залишається однією з проблем у галузі теорії управління. Новизна роботи полягає у розробці та експериментальній реалізації дворівневого підвищувального перетворювача постійного струму, керованого ПІД-регулятором, для отримання максимальної потужності фотоелектричних пристроїв. Мета. Аналіз та управління дворівневою топологією підвищення з використанням відновлюваного джерела енергії та розрахунок параметрів ПІД-регулятора простим та точним методом. Методи. Коефіцієнти ПІД оптимізуються за допомогою методу діаграми коефіцієнтів (CDM) у середовищі MATLAB. Отримані результати. Розроблено та проаналізовано математичну модель дворівневого підвищувального перетворювача з ПІД-регулятором та фотоелектричним джерелом енергії. Модель дозволяє спроєктувати параметри контролера пропонованої системи. Практична цінність. Прототип, керований пропонованим контролером CDM-PID, протестували з використанням вбудованої плати Arduino. Наведено порівняння результатів моделювання з експериментальними даними. Отримані результати показують, що експериментальні результати близько відповідають моделюванню, а пропонований CDM-ПІД-регулятор забезпечує швидкі та точні результати. Бібл. 24, табл. 2, рис. 16.
Keywords: power electronics; energy conversion; two-level boost converter; coefficient diagram method controller; силова електроніка; перетворення енергії; дворівневий підвищувальний перетворювач; регулятор методу діаграми коефіцієнтів